PENINGKATAN PRODUKSI ASI DENGAN METODE PIJAT LAKTASI - Fivin Susanti; Nova Yulita (Jurnal Ilmiah Kesehatan, 2024)
Lactation massage is massage performed on several parts of the body, namely the head, neck, shoulders, back, and breasts. Lactation massage can be done when the breasts are swollen or not smooth, and the mother wants to relax. The aim of this case study is to provide midwifery care to postpartum women by performing lactation massage. The midwifery care method used is in the form of a case study of postpartum mothers who experience problems in expressing milk by doing lactation massage and using the SOAP method as documentation. The results obtained by the lactation massage were successful in producing breast milk smoothly and in large quantities. The conclusion of lactation massage is that there is an effect of lactation massage on the smoothness of breastfeeding in postpartum mothers who experience problems with insufficient breastfeeding and minimize complications during the puerperium.